(3GdhLjR aj TQM COGA GdbQCI GdKeGfjI CFeI GdCeUGQ GdNeSIs - (3GdMSf Hf Ydj Hf EHQGgje Hf jROGO GdCghGRj, CHh Ydj,J (B446 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdQMje GHJOj HPcQg eG GNJda ajg GdbQGA GdKeGfjI GdeTghQhf s
(3BNQgG (B:s
(3hhbaJ obfHd HGdJcHjQ Ydi eLGgO hQaYg GdHRj Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3aj BNQgG oebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B245 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B247s
Keywords: (3GdbQGAGJ hGdJLhjOs